THE SUITABILITY OF THE LAND USAGE AND THE PRODUCTIVITY OF MELON FARMING IN THE FORMER LAGOON LAND IN PARANGTRITIS, KRETEK DISTRICT, BANTUL REGENCY, DIY 2010 - Fenti Rahayu; Suparmini Suparmini; Sugiharyanto Sugiharyanto (Universitas Negeri Yogyakarta, 2013)
This research aims to know the suitability of land usage in the former lagoon plains in Parangtritis for melon cultivation; land border factors; land improvement efforts; the management of melon cultivation and the productivity of melon in the research areas. This research is descriptive quantitative research. The population in this research consists of physical and non-physical population. Physical population includes all former lagoon lands planted with melons or 6,300 m². Moreover, non-physical population consists of all melon farmers in the research areas which consist of 3 farmers. This research employs purposive sampling techniques to take the non-physical research samples i.e. the former lagoon soil from the southern plains in the form of sand and the soil from the former lagoons in the northern part in the form of clay. Moreover, the non-physical population samples were not taken because there are only 3 farmers in the research areas. The techniques of data collection include observation, laboratory testing, interviews and secondary data collection. The data analysis for the physical aspects was performed through laboratory analysis while for the non-physical aspects were conducted through descriptive statistical analysis. The findings show that (1) the southern parts of the research areas have a land suitability level of S3 (marginally suitable), and the northern parts of the research areas have a land suitability level of S2 (quite appropriate); (2) the factors which become the land borders are rainfall, drainage, soil texture, and content of C-organic and the danger of flood; (3) land improvement efforts were performed by planting melons in the dry season to cope with heavy rainfall in the rainy season, fertilizing plants using manure to inhibit drainage and increase the content of C-organic in the soil, making water drainage on farms to prevent from flood; (4) The crop management is performed using modern techniques, planting melon is only done once every year in the dry season so that the plants are not in danger of flooding during the rainy season, and the optimal results can be achieved; (5) The net production of melon per year performed with good management can reach 3.2 tons per 1,000 m² land. The gross income of farmers per 1,000 m² of land is Rp. 6,080,000.00. The production and labor cost for each planting is Rp. 2,348,775.00 per 1,000 m² of land. Therefore, net income of melon farmers in the research area reaches Rp. 3,731,225.00.Keywords: landuse, productivity, lagoon